TAX IN INDONESIA IN ISLAMIC PERSPECTIVE - Eka Shofiana, Dina (Entrepreneur, 2011)
AbstractBased on the order of magnitude revenue, taxes in Indonesia there are three major objects, namely Income (Act No.38 of 2008), Value Added Goods and Services and Sales on luxury goods (Act No.18 of 2000) and Land and Building (Law no. 20 of 2000). If we look deeper, and the subject, the subject of income tax clearly does not distinguish between Muslims and non-Muslims, so that in this law, Muslims could be taxed twice (double taxs) to charity. From the tax objects above shows that almost all types of additional economic capacity (reception) the person or business entity, is subject to tax part of which is also the object of charity, such as the income will be subject to zakat profession, income from operations which are subject to zakat commerce, and others. Income tax is also not question the source of halal and haram or income, such as bank interest, which has been forbidden by a panel of scholars difatwakan or income and effort that clearly unlawful, such as liquor, gambling, and so forth. This clearly contradicts with Islamic Sharia. In addition, the gift also is used as the object of income tax, whereas in Islam, the gift was recommended by the Prophet., To evoke a sense of compassion. In other words, there are many objects of this tax is not in accordance with Islamic Shari´ah, which needs review.Keywords: Tax, Zakat, the Islamic Shari´ahAbstrakBerdasarkan urutan besarnya pendapatan, pajak di Indonesia ada tiga obyek utama, yaitu penghasilan (UU No.38 tahun 2008), Pertambahan Nilai Barang dan Jasa dan Penjualan atas Barang Mewah (UU No.18 Tahun 2000) dan Bumi dan Bangunan (UU No. 20 dari 2000). Jika kita melihat lebih dalam, dan subjek, subjek pajak penghasilan jelas tidak membedakan antara Muslim dan non-Muslim, sehingga dalam undang-undang ini, umat Islam bisa dikenakan pajak dua kali (taxs ganda) untuk amal. Dari obyek pajak atas menunjukkan bahwa hampir semua jenis kemampuan ekonomi tambahan (resepsi) badan orang atau bisnis, tunduk pada bagian pajak yang juga merupakan obyek amal, seperti pendapatan yang akan dikenakan zakat profesi, pendapatan dari operasi yang dikenakan zakat perdagangan, dan lainnya. Pajak penghasilan juga tidak mempertanyakan sumber halal dan haram atau pendapatan, seperti bunga bank, yang telah dilarang oleh panel ulama difatwakan atau penghasilan dan usaha yang jelas melanggar hukum, seperti minuman keras, perjudian, dan sebagainya. Ini jelas bertentangan dengan Syariah Islam. Selain itu, hadiah juga digunakan sebagai objek pajak penghasilan, sedangkan dalam Islam, hadiah itu direkomendasikan oleh Nabi, Untuk membangkitkan rasa belas kasih.. Dengan kata lain, ada banyak obyek pajak ini tidak sesuai dengan syariah Islam, yang perlu diperiksa.Kata kunci: Pajak, Zakat, syariat Islam